Risk factors associated with sepsis in children with acute lymphoblastic leukemia and febrile neutropenia - Versary, An nieza Dea; Susanah, Susi; Alam, Anggraini (Indonesian Pediatric Society, 2024)
Background Children with acute lymphoblastic leukemia (ALL), especially those with febrile neutropenia, are susceptible to sepsis. Several factors have been associated with the occurrence of sepsis in children with leukemia. Objective To identify potential risk factors associated with sepsis in children with ALL and febrile neutropenia. Methods This cross-sectional study was done in children with ALL who sought treatment at Dr. Hasan Sadikin General Hospital, Bandung, Indonesia from January 2019 to March 2022. We recorded patients’ gender, age, nutritional status, absolute neutrophil count (ANC), co-infection, prophylactic antibiotic use, and phase of chemotherapy. Results Of 131 subjects, 57.3% were male and 42.8% were wasted. Subjects had a median age of six years old and median ANC of 230 cells/mm3. Furthermore, 48.9% of subjects had co-infections, 87.8% had not received prophylactic antibiotics, and 48.9% were in the induction phase of chemotherapy. Multiple logistic regression analysis revealed that older age [OR 1.16 (95%CI 1.04 to 1.29); ?=0.149; P=0.008] and co-infection [OR 12.9 (95%CI 5.01 to 33.21); ?=2.551; P<0.001] were significantly associated with sepsis in children with ALL and febrile neutropenia. Bronchopneumonia was the most common co-infection (72.5%). Conclusion Older age and co-infection are significantly associated with sepsis in children with ALL and febrile neutropenia.